TED TALKS VIDEO AND STUDENTS’ LISTENING SKILLS - Dimas Fahmiansyah; Tryanti R Abdulrahman (Lingua, 2018)
The advancement of technology makes the use of media growing rapidly, but its application in the field of learning, especialy English is still fairly minimal. Recently, the use of technologies has grown to be popular in ESL / EFL teaching, TED (Technology, Entertainment, and Design) is one of them. Hence, the aim of this research is to find out whether there is or no effect of the use of TED Talks video on grade eleven students’ listening skill. The research was conducted at SMAN 89 Jakarta in the academic year 2017/2018. The population of this research consists of 216 students sitting on six classes. The samples of the research were taken by the means of cluster random sampling from the population with the total sample number of 70 students consisted of 35 students each class. The adopted research methodology was quasi-experimental research, with the research design being randomized post-test only control group design. The statistic method used to analyze the data was One-Way ANOVA using SPSS through the testing of Null Hypotheses, which was preceded by the normality test and homogeneity test as the pre-requisite to the data analysis. The result of the test showed that H0 is rejected and Ha is accepted which proves that there is significant effect of the use of TED Talks on grade eleven students’ listening skill.